Measurements from preterm infants to guide face mask size. Issue 4 (10th April 2015) - O'Shea, Joyce E; Thio, Marta; Owen, Louise S; Wong, Connie; Dawson, Jennifer A; Davis, Peter G
Abstract : Objective: International guidelines recommend that an appropriately sized face mask for providing positive pressure ventilation should cover the mouth and nose but not the eyes and should not overlap the chin. This study aimed to measure the dimensions of preterm infants' faces and compare these with the size of the most commonly available face masks (external diameter 50 mm) and the smallest masks available (external diameters 35 and 42 mm). Methods: Infants 24–33 weeks' postmenstrual age (PMA) were photographed in a standardised manner. Images were analysed using ImageJ software (National Institute of Health, USA) to calculate the distance from the nasofrontal groove to the mental protuberance. This facial measurement corresponds to the external diameter of an optimally fitting mask. Results: A cohort of 107 infants between 24 and 33 weeks' gestational age, including at least 10 infants per week of gestation, was photographed within 72 h after birth and weekly until 33 weeks' PMA. 347 photographs were analysed. Infants of 24, 26, 28, 30 and 32 weeks' PMA had mean (SD) facial measurements of 32 (2), 36 (3), 38 (4), 41 (2) and 43 (4) mm, respectively. There were no significant differences when examined by gender or when small for gestational age infants were excluded. Conclusions: The smallest size of some brands of mask is too large for many preterm infants. Masks of 35 mm diameter are suitable for infants <29 weeks' PMA or 1000 g. Masks of 42 mm diameter are suitable for infants 27–33 weeks' PMA or 750–2500 g.